Prevalence of painful peripheral neuropathy in a screening program looking at risk for developing diabetic foot in a public Peruvian hospital - Rivera-Grimaldo, Luisa S. (2024)
Objective: To determine prevalence of painful asymptomatic peripheral neuropathy (PN) in persons with type 2 diabetes mellitus (DM2) and its associated characteristics. Materials and Methods: This is a cross-sectional descriptive study performed in patients belonging to the program ‘Feet at risk’ at the Endocrinology Service in Maria Auxiliadora National Hospital. Patients with DM2 who were seen between 2015 and 2020 were included. The definition of PN is according to Toronto Consensus, considering the evaluation of three components: symptoms, signs and Achilles reflex, determining certainty as possible and probable, according to the combinations found. For assessing symptoms, the total symptom score (TTS) was used; for signs, monofilament test was used, and vibration sensitivity was assessed using a 128-Hz tuning fork. Prevalence of PN was calculated according to symptoms and certainty of the diagnosis. Also, the clinical characteristics of patient groups were described. Results: One-thousand and six persons were included, their mean age was 60,5 years, and 69,3% were female. In those who had at least one item from Toronto criteria, 60,5% had painful PN, and 21,8% had asymptomatic PN. When using more diagnostic certainty, i.e., two from three criteria being positive, the prevalence of painful PN was 42,2% and for asymptomatic PN, it was 6,5%. Four groups with different distributions with respect to sex, time with diabetes, ulcer history, peripheral arterial disease and glycemic control were established. Conclusion: In patients from the Endocrinology Service at Maria Auxiliadora Hospital 42,2% and 6,5% had more certainty for presenting with probable painful PN and asymptomatic PN, respectively. Further studies are needed for confirming the usefulness of the aforementioned criteria for properly estimating the burden of disease.